Use of zinc oxide nanoparticles for detection of fluoride in toothpaste gel - Wasupon Watjanavarreerat; Liviu Steier; Kitsakorn Locharoenrat (Journal of Environmental Science and Health Part A, 2022)
This study aimed to investigate the metal-binding effect of fluoride, contained in different commercial toothpaste gels; the study aimed to determine if the toothpastes contained excessive concentrations of fluoride, which result in white spot lesions. A spectrophotometric method that used spectrophotometric reagents, including zinc oxide nanoparticles and iron chloride, was used to determine fluoride distribution; the analysis was based on the selective attack of fluoride ions on metals. Fluoride concentrations between 0 and 1450 ppm were analyzed. Although the iron-fluoride complex was a more sensitive reagent, the zinc-fluoride complex could serve as a suitable alternative to it for fluoride analysis, partly because the method was less time consuming and more stable. The detection and quantification limits obtained from the linear calibration curves of the zinc-fluoride complexes, in deionized water, were 0.191:1 and 0.579:1 w/w ZnO, respectively. A model calibration curve was suggested to detect the unknown products of fluoride degradation. Dentists could use a fluoride treatment similar to the protocol used in this study, to prevent potential enamel demineralization, and exclude physical cavity preparation and restoration.
Keywords: Fluoride Effects and Removal; Mercury impact and mitigation studies; Heavy Metal Exposure and Toxicity